Interpersonal Coordination between Female Soccer Players: Leader-Follower Roles within a Collision-Avoidance Task - Courtney A Fernandes; Grant E Norte; Sarah M Schwab; Alli Gokeler; Amanda Murray; David M Bazett-Jones; David A Sherman (North American Sports Medicine Institute, 2024)
# Background/Purpose Return to sport decision-making may be improved by assessing an athlete's ability to coordinate movement with opponents in sport. The purpose was to investigate whether previous injuries associated with female soccer players' interpersonal coordination during a collision avoidance task. The authors hypothesized that external perturbations would disrupt the strength and stability of coordinated movement, and that individuals with a history of injury would be less likely to recover coordinated movement. # Study Design Cross-Sectional # Methods Nine female athletes with a history of lower extremity injuries and nine without injuries were paired into dyads. Each dyad completed twenty trials of an externally paced collision-avoidance agility task with an unanticipated perturbation. Participant trajectories were digitized and analyzed using cross-recurrence quantification analysis (CRQA) to determine the strength and stability of interpersonal coordination dynamics. Trials in which participants with injury history assumed leader or follower roles within each dyad were then used to study how dyadic coordination varied across task stages (early, perturbation, and late) using linear mixed effect models. Cohen's d effect sizes were calculated to demonstrate magnitude of differences. In exploratory analysis, psychological readiness (i.e., self-reported knee functioning, fear of injury, and risk-taking propensity) was evaluated for their association with leader-follower status. # Results Perturbation disrupted the strength (R2=0.65, p<0.001, early=49.7±1.7, perturbation=41.1±1.7, d=0.39) and stability (R2=0.71, p < 0.001, early=65.0±1.6, perturbation=58.0±1.7, d=0.38) of interpersonal coordination regardless of leader-follower status. Individuals with injury history failed to restore coordination after the perturbation compared to control participants (injury=44.2.0±2.1, control=50.8±2.6, d=0.39). Neither demographic nor psychological measures were associated with leader-follower roles (B=0.039, p=0.224). # Conclusion Individuals with a history of lower extremity injury may have a diminished ability to adapt interpersonal coordination to perturbations, possibly contributing to a higher risk of re-injury. # Level of Evidence 3